3D nanoporous hybrid nanoflower for enhanced non-faradaic redox-free electrochemical impedimetric biodetermination - Subramani, I.G. (Taiwan Institute of Chemical Engineers, 2020)
Recently, non-faradaic electrochemical impedimetric (nfEIS) has been identified as a dynamic and robust method for bio-determining. However, the success of a nfEIS approach largely depends on its sensing layer architecture. In this study, the use of a Glutaraldehyde (GA) crosslinked copper (Cu) â bovine serum albumin (BSA) hybrid nanoflower with three-dimensional nanoporous architecture for the sensing layer was investigated. The nanoflower morphology changes were observed under FESEM, revealing loosely interlaced nanoflower into a tightly interlaced, highly porous structure upon GA crosslinking. This nanoflower was hybridized to immobilize aminated-DNA probe on the transducer surface and detect the target TB DNA in their natural redox-free environment. FTIR and XPS characterization showed distinct peaks at 950â1100 cmâ1 (P-O, P=O bonds from nanoflower and DNA backbone) and 286.48 eV (interaction between BSA and aminated DNA), respectively, validating the successful DNA probe immobilization on the nanoflower surface. Furthermore, impedimetric sensing in a redox-free environment showed that the developed TB biosensor present has a detection limit (LOD) of 60 pM with a (linear) range from 1 pM to 1 ÂµM with good reproducibility. This redox-free non-faradaic EIS offers excellent biosensing potential and may be extended for diagnosing other biomarkers in clinical practice. Â© 2020 Taiwan Institute of Chemical Engineers